Greater risk of sementia when spouse has dementia? the cache county study: [See editorial comments by Dr. Peter P. Vitaliano, pp 976-978]: BRIEF REPORTS - Norton, M.C. (2014)
10.1111/j.1532-5415.2010.02806.x